Relationship between emotional intelligence and job well-being in Chinese clinical nurses: multiple mediating effects of empathy and communication satisfaction - Xue Li; Hongjuan Chang; Quanying Zhang; Jianli Yang; Rui Liu; Yajie Song (BMC, 2021)
Abstract Background Nursing work is associated with great pressure, and nurses are often overwhelmed. Therefore, correct emotional regulation is essential to improve nurses' job well-being and promote better engagement in nursing work. The purpose of this study was to establish a structural model to estimate the impact of Chinese clinical nurses' emotional intelligence on job well-being, using multiple intermediaries to explain the internal mechanisms underlying the relationship. Methods This was a cross-sectional study of 1475 registered nurses from a Chinese hospital who provided responses to emotional intelligence, empathy, communication satisfaction, and job well-being scales. Path analysis using a multiple mediation model was performed using AMOS 23.0. Results Among all clinical nurses who participated in the survey, 1475 (98.33 %) completed the questionnaire. The nurses' job well-being score was 83.61 ± 12.63. There was a significant positive correlation between job well-being and communication satisfaction, emotional intelligence, and empathy ability (r = 0.346-0.570, P < 0.001). Empathy and communication satisfaction partially mediated the relationship between emotional intelligence and job well-being, with effect sizes of 0.047 and 0.227, respectively. The chain mediating effect of empathy and communication satisfaction had a value of 0.045. Conclusions It is recommended that hospital managers take actions to improve nurses' emotional intelligence level, and conduct professional psychological training to improve nurses' empathy and communication satisfaction, and ultimately improve their job well-being.